Building Student Responsibility Through Aqidah Akhlak Guidance: Membangun Tanggung Jawab Siswa Melalui Bimbingan Aqidah Akhlak - Hayati, Nilna Zahril; NISAK, Nur Maslikhatun Nisak (Indonesian Journal of Islamic Studies, 2025)
General Background: Education plays a central role in shaping students’ character and moral responsibility, especially within Islamic-based schools. Specific Background: At SD Muhammadiyah 1 Waru Sidoarjo, Aqidah Akhlak teachers are expected not only to teach religious knowledge but also to cultivate responsibility in students’ learning behavior. Knowledge Gap: However, many students still demonstrate low responsibility, such as incomplete homework and lack of classroom discipline, indicating the need for deeper exploration of teacher strategies in this process. Aims: This study aims to analyze how Aqidah Akhlak teachers develop students’ learning responsibility through various pedagogical approaches. Results: Using a qualitative descriptive method, data from interviews, observations, and documentation reveal that teachers apply modeling, group discussions, and independent assignments effectively, resulting in noticeable improvement in students’ responsibility, discipline, and participation. Novelty: The study emphasizes the integrative application of religious values with character formation through active learning methods. Implications: The findings suggest that moral education embedded in Aqidah Akhlak subjects can strengthen students’ academic responsibility and personal ethics when consistently applied in the learning environment. Highlights: Aqidah Akhlak teachers act as moral role models in learning. Integrative methods effectively shape students’ responsibility. Religious-based character education supports academic discipline. Keywords: Aqidah Akhlak, Teacher Role, Learning Responsibility, Character Education, Elementary Students